2011
DOI: 10.1002/jctb.2682
|View full text |Cite
|
Sign up to set email alerts
|

Selective CO oxidation over monolithic AuMgO/Al2O3 catalysts

Abstract: BACKGROUND: Selective CO oxidation was studied in a hydrogen-rich environment over monolithic Au/MgO/Al 2 O 3 catalysts at 50-150• C. The wash-coating of cordierite monoliths with colloidal Al 2 O 3 was followed by wet impregnation of MgO; the subsequent deposition of Au was achieved using various methods. All catalysts were characterized using ICP and ESEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Colloidal alumina is available commercially, and it can be dispersed in a solution containing water. For example, Özdemir et al have used colloidal alumina dispersed in water to coat monoliths for carbon monoxide oxidation [100]. Barbero et al have reported successful coating of their metallic monoliths with the use of colloidal alumina as a primer and a stabilizer [101].…”
Section: Coating γ-Alumina As a Secondary Supportmentioning
confidence: 99%
“…Colloidal alumina is available commercially, and it can be dispersed in a solution containing water. For example, Özdemir et al have used colloidal alumina dispersed in water to coat monoliths for carbon monoxide oxidation [100]. Barbero et al have reported successful coating of their metallic monoliths with the use of colloidal alumina as a primer and a stabilizer [101].…”
Section: Coating γ-Alumina As a Secondary Supportmentioning
confidence: 99%
“…Based on the fundamental studies of Bond et al , the pioneering work of Haruta et al , and seminal studies of Hutchings gold catalysis has been widely investigated . Rossi et al reviewed the key aspects of selective oxidations using supported gold catalysis.…”
Section: Introductionmentioning
confidence: 99%